Pengaruh Pendapatan Asli Daerah (PAD), Dana Perimbangan, Dan Sisa Lebih Perhitungan Anggaran (SiLPA) Terhadap Belanja Modal Pada Pemerintah Kabupaten Bandung Barat Tahun 2014-2021 - Ulhaq, Hafizh Dhiya; Sudradjat (Indonesian Accounting Research Journal, 2025)
The main sources that can fill regional finances and can be used as a source of financing for regional expenditures including capital expenditures are Local Own Revenue (PAD), Balancing Funds, and Utilization of Overtime Budget Calculations (SiLPA). This study aims to determine the effect of regional original income, balancing funds, and SiLPA on capital expenditure in West Bandung Regency in 2014-2021. This research is a quantitative research with a descriptive approach. The data to be used comes from the 2014-2021 APBD Realization Report. Data collection techniques in this study used literature study techniques and documentation methods. The method of analysis is descriptive analysis. The prerequisite analysis test uses the classical assumption test, namely the normality test, multicollinearity test, heteroscedasticity, and autocorrelation statistical tests. Multiple regression analysis and hypothesis testing using the coefficient of determination test, t statistical test and f statistical test. The results of the study show that Regional Original Income (PAD), Balancing Funds, and SiLPA both partially and simultaneously have an effect on capital expenditure.